Arthroscopic Assisted Reduction of Talus Fractures Leads to Improved Clinical Outcomes at Mid- Term Follow-Up - Hayden Hartman BS; Haley N. Tornberg BS; Paul Fine-Lease BA; Arianna Gianakos DO (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: Talus fracture is an uncommon and challenging pathology to treat due to its relationship with articular cartilage, ligamentous network, and avascular nature. The purpose of this systematic review was to evaluate the clinical outcomes after arthroscopic talar fracture fixation, compare to conventional open reduction and internal fixation (ORIF), and analyze the quality and level of evidence of the included studies. Methods: A systematic review of the MEDLINE, EMBASE, and Cochrane Library databases was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in June 2023. Articles were included if they evaluated outcomes following arthroscopic treatment of talus fractures, were written in English, were peer-reviewed, had a minimum of 2 patients per cohort, had human patients, and had a minimum 6-month follow-up. Inclusion criteria consisted of: Studies reporting clinical data following arthroscopy for the treatment of talus fractures were included and assessed. Results: Seven studies were analyzed, including 4 case series, 1 retrospective cohort, and 2 retrospective comparative studies. 237 patients treated with arthroscopic assisted reduction were compared to 76 patients treated with ORIF. Amongst arthroscopically treated patients, the AOFAS score improved from 71.2 ± 5.2 preoperatively to 89.9 ± 4.3 postoperatively. The SF-36 score improved from 73.2 ± 30.3 preoperatively to 104.5 ± 19.3 postoperatively. In total, 6 complications (3.0%) were observed in arthroscopically treated patients, of which the most common was peri-talar osteoarthritis in 2 patients (0.84%). In comparative cohorts, ORIF patients experienced a 13.0% complication rate in 6 patients (talar necrosis, malunion, nonunion, infection, and post-traumatic arthritis), compared to 2.2% in 1 patient (malunion) in the arthroscopic cohort. Conclusion: This study demonstrates that arthroscopic assisted reduction of talar fractures results in good clinical outcomes with lower complication rates. This minimally invasive approach had lower complications than ORIF, with no cases of talar necrosis and decreased postoperative traumatic arthritis. This technique provides adequate exposure without additional osteotomy, while decreasing trauma to local anatomical trauma, minimizing the risk of postoperative complications, and improving fracture healing assessment of concomitant lesions. These findings indicate arthroscopic treatment of talus fractures is an efficacious and safe procedure with comparable or improved clinical and postoperative outcomes as compared to conventional ORIF.